Phytochemical Features of Moringa oleifera Leaves as Anticancer - Edwinanto, Ludovicus; Septiadi, Endry; Nurfazriah, Latifah R.; Anastasya, Karina S.; Pranata, Natallia (Journal of Medicine and Health, 2018)
Cancer is a disease that can threaten human life. Various methods of cancer therapy havebeen widely practiced, one of which is chemotherapy. But the cost used for the therapy is alsovery expensive. This difficulty led many researchers to conduct research to find activecompounds from natural materials. Moringa leaf (Moringa oleifera) has cytotoxic activity,because it contains a lot of flavonoids. Flavonoids are polyphenol compounds produced fromsecondary metabolism in plants. The most flavonoids that are anticancer active substances inthe Moringa leaf are quercetin, kaempferol and myricetin. Cytotoxic activity because theseactive substances can induce apoptosis through intrinsic pathways by inhibition of mitogen-activated protein kinase (MAPK), extracellular-signal-regulated kinase 1/2 (ERK 1/2), c-Jun N-terminal protein kinase 1 (JNK), and protein kinase C (PKC).Keywords: Moringa leaf, quersetin; kaempferol; myricetin; anticancer